2006
DOI: 10.1038/sj.ki.5001833
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-inhibitor induced pain syndrome after organ transplantation

Abstract: Among 243 patients who received kidney transplants at our center, two patients suddenly developed a severe debilitating pain syndrome in the lower limbs. Case no. 1A 49-year-old male patient who received a deceased donor kidney transplant, in therapy with tacrolimus (plus steroids and perioperative basiliximab). One month after transplantation he reported joint pain in his ankles, knees, feet, and hands. The pain became so intense that the patient was forced to use crutches to walk. Clinical examination reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 17 publications
2
49
1
Order By: Relevance
“…In addition, calcineurin inhibitors, such as cyclosporin A and FK-506 (tacrolimus), are the most commonly used immunosuppressive drugs to prevent the rejection of transplanted organs and tissues. However, these drugs can cause unexplained persistent pain and pain hypersensitivity, often referred to as calcineurin inhibitor-induced pain syndrome (Grotz et al, 2001;Collini et al, 2006). Indeed, systemic administration of FK-506 can cause long-lasting pain hypersensitivity through potentiating NMDAR activity in the spinal dorsal horn .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, calcineurin inhibitors, such as cyclosporin A and FK-506 (tacrolimus), are the most commonly used immunosuppressive drugs to prevent the rejection of transplanted organs and tissues. However, these drugs can cause unexplained persistent pain and pain hypersensitivity, often referred to as calcineurin inhibitor-induced pain syndrome (Grotz et al, 2001;Collini et al, 2006). Indeed, systemic administration of FK-506 can cause long-lasting pain hypersensitivity through potentiating NMDAR activity in the spinal dorsal horn .…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin inhibitors, such as tacrolimus (FK506) and cyclosporine A, are commonly used immunosuppressants and have greatly improved the long-term survival of patients after organ and tissue transplantation. However, these drugs can result in unexplained severe pain and pain hypersensitivity, clinically known as calcineurin inhibitor-induced pain syndrome (CIPS) (Grotz et al, 2001;Collini et al, 2006;Noda et al, 2008;Kakihana et al, 2012). CIPS predominantly affects the lower limbs, and the pain is particularly excruciating during standing and walking (Grotz et al, 2001;Fujii et al, 2006;Noda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5,9,10 Those reports suggest that the effects of calcineurin inhibition on vascular tone play an important role in the development of CIPS. 8 However, only one patient received diltiazem in our study, and thus, we could not assess the efficacy of calcium channel blockers for CIPS in the setting of allo-HSCT. This study confirmed that discontinuation, dose reduction, or switching to another CI is effective for management of CIPS.…”
Section: Discussionmentioning
confidence: 96%